The Effect of Training And Competence on Teacher Performance at MTS N 32 Jakarta During Distance Learning - Rafi, Fauzan Abdu; Fadlillah, Alnisa Min; Sumilir, Sumilir (Universitas Mercu Buana, 2021)
Abstract – This research was carried out to fulfill the curiosity about how the influence of training and competence in influencing teacher performance, especially during PJJ (Distance Learning) which took place at Gunung N 32, Jakarta. Using quantitative research methods in its implementation, as well as the population and samples were taken using a saturated sample purposive sampling technique involving 33 teachers as respondents, then analyzed descriptively and inferentially using Smart PLS 3.0 software. The results of this study partially show the effect of the training variable having the original sample value of 0.368 so that it is declared to have a positive and significant effect and the competence that has the original sample value of 0.546 which can also be declared positive and significant on the teacher's performance during PJJ with a coefficient of determination of 0.605 or 60, 5% and 39.5% are influenced by other variables.